Resistance to globalization political struggle and cultural resilience in the Middle East, Russia, and Latin America - Barrios, Harald; Beck, Martin; Boeckh, Andreas; Segbers, Klaus (Politik (Münster in Westfalen, Germany), 2003)
This volume is an important contribution to the empirical research on what globalization means in different world regions. "Resistance" here has a double meaning. It can signify active, intentional resistance to tendencies which are rejected on political or moral grounds by presenting alternative discourses and concepts founded in specific cultural and national traditions. It can also mean resilience with regard to globalization pressures in the sense that traditional patterns of development and politics are resistant to change. The book shows the that the local, sub-national, national, and regional patterns of politics and development coexist with globalized structures without yielding very much ground and in ways which may turn out to be a serious barrier to further globalization. Case studies presented focus on Venezuela, Brazil, the Middle East, Iran, and Russia."--Jacket